2022
DOI: 10.1021/acs.langmuir.2c01243
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Interconnected Pickering Polymerized High Internal Phase Emulsions by Arrested Coalescence

Abstract: Emulsion templating is a method that enables the production of highly porous and interconnected polymer foams called polymerized high internal phase emulsions (PolyHIPEs). Since emulsions are inherently unstable systems, they can be stabilized either by surfactants or by particles (Pickering HIPEs). Surfactant-stabilized HIPEs form materials with an interconnected porous structure, while Pickering HIPEs typically form closed pore materials. In this study, we describe a system that uses submicrometer polymer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…SEM was used to explore the morphology of the fabricated scaffolds. ,, All samples were gold-coated to increase the conductivity. For morphological investigation of G1, G2, and G3, a FEI Inspect F SEM (Philips/FEI XL-20 SEM, Cambridge, UK) was used and, for G4, Jeol SEM was used (JSM-6510, Japan) with 10 kV power.…”
Section: Methodsmentioning
confidence: 99%
“…SEM was used to explore the morphology of the fabricated scaffolds. ,, All samples were gold-coated to increase the conductivity. For morphological investigation of G1, G2, and G3, a FEI Inspect F SEM (Philips/FEI XL-20 SEM, Cambridge, UK) was used and, for G4, Jeol SEM was used (JSM-6510, Japan) with 10 kV power.…”
Section: Methodsmentioning
confidence: 99%
“…Milled polyHIPE particles alone (Supporting Information, Figure S1a,b) revealed a typical heterogeneous distribution of spherical porous polymer particles, similar to previously reported polyHIPE morphologies. 13,36 SEM analysis of composite gels revealed that a significant number of polyHIPEs were only partially embedded within the surface of the cellulose composite gel; polyHIPEs on the surface of the cellulose gel are not fully covered by a film of polymer and can be seen protruding from the surface (Figure 3c (red asterisk) and Supporting Information, Figure S4e−h). Conversely, SEM imaging of the composite gelMA gels revealed that polyHIPE particles were fully embedded into the gel, with a complete gelMA film coating all polyHIPEs near the surface of the gel (purple asterisks).…”
Section: Both Gels Tested Support the Growth Of Amentioning
confidence: 99%
“…During the process the polymer sets, and the water is removed to obtain the remaining polymer network template formed by the emulsion. When using large amounts of internal phase (over 74% of the total volume) and a suitable emulsifying surfactant, this process produces High Internal Phase Emulsions (HIPEs) 1,[8][9][10] . These are templates to produce highly porous polymer structures (polyHIPEs) with potentially interconnected porosity 1,11 .…”
Section: Introductionmentioning
confidence: 99%